Monitoring oil quality and product oil uptake during vacuum frying process optimization of mango (Mangifera indica L. cv. Carabao) - De Mesa, Angeline P.; Tabardillo, Joyce Abigail A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018.)
To provide insight on the possible influence of repeated oil use on the properties of the vacuum fried mango chips, this study aimed to monitor the quality of frying oil during the optimization of vacuum frying process. Indices of frying oil quality such as total color difference (ΔE), free fatty acid (FFA) content and 2-thiobarbituric acid (TBA) value were determined using HunterLab Colorimeter, manual titrimetry and direct method, respectively. Oil absorbed by the mango chips was also determined through Soxhlet method. FFA content and TBA value of the oil extracted from the product were also determined. Results established significant color darkening with repeated use of oil. Minimal effects on FFA values and TBA values of both the frying oil and the oil extracted from the products were observed. Also, FFA values reported were within the acceptable limits for frying oil. Oil absorbed by the products fried using repeatedly used oil varied significantly; but results on the effect of the number of oil use and vacuum frying parameters with the oil uptake were inconclusive. Overall, this study revealed that repeated use of oil during process optimization of vacuum frying has negative effect on the indices of frying oil quality such as oil color and free fatty acid content. With the FFA results, it can be said that the frying oil is still acceptable and usable after at most 12 runs. However, further use of the same oil in future production may compromise the vacuum fried mango chips' quality and safety. Moreover, varying degrees of oil absorbed showed that monitoring of frying oil quality during process optimization will be necessary in future product development activities in order to establish how vacuum frying parameters and repeated oil use really affect oil uptake.
submitted June 2018
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Mango; Oil quality